Relanzamiento de restobares en Miraflores en situación pandémica - Acevedo Montoya, Sandra Paola (2022)
Since March 2020, Peru has been in a state of national health emergency because of the COVID-19 pandemic. This caused a paralyzation of commercial activities, including the restaurant and restobar sector. This had an impact on consumer behavior and experience, generating a new dynamic in the market and leading companies to redefine their activities, taking into account the new measures dictated by the government and the demands of the context. Subsequently, after the national vaccination process, the restriction of these measures become more relaxed, among them: curfews, limited room capacity, table distancing, biosecurity protocols and the use of masks. The problem of the present research is framed in the search for the minimum requirements that a restobar must meet to offer an adequate experience, taking into account the new normality of the pandemic. In turn, the general objective is to determine the essential conditions for a customer to place an order in a restobar in Miraflores, in the COVID-19 situation. The study variables were the impact of Covid-19 on the attendance of a restobar, the level of service quality and the level of post-sales satisfaction.The methodology used is mixed, the first part being qualitative research measured through three focus groups. Then, with the insights gathered, a survey was applied to the target audience: men and women between 18 and 45 years of age from social economic status ABC, who live in Lima and whose frequency of visit is at least once a month to restobars in general in the context of pandemic and on the other hand, who attend restobars in Miraflores without a specific frequency. The main findings are that the client expects a restobar in Miraflores to communicate measures to counteract COVID-19 such as distributing tables, taking into account a considerable distance, having open spaces such as terraces and complying with biosecurity measures. On the other hand, the staff is expected to be friendly, efficient in their service and to communicate the promotions of the premises. It is important to consider that consumers value having a differentiated theme. Regarding after-sales service and delivery, it was identified that they are not relevant for the public studied, since problems are solved in the same store. In addition, conflicting opinions were found regarding delivery, i.e. one group thought that it was a good alternative to avoid